An innovative approach to measure skill about artificial insemination in buffaloes - V B DIXIT; R K SHARMA; A BHARADWAJ; P SIKKA; S K PHULIA (Indian Journal of Animal Sciences, 2016)
Data pertaining to 3 trainings on artificial insemination (AI) were analyzed and 44 farmers constituted as the study sample. The respondents selected for the study were those who had earlier exposure to AI as they were doing it in the field but needed further refinement of skills. To study skill development in AI, the process was broken into different steps, viz. estrus check, washing of buffaloes, thawing, loading, passage of AI gun and important precautions. Each step was assigned scores of 10, 10, 10, 40, 10 and 20, respectively, by seeking the response from 30 scientists working in the Institute and LUVAS (Lala Lajpat Rai University of Veterinary and Animal Sciences, Hisar). Scores were assigned to each step and summated to arrive at final score of a respondent based on their skill of each step. Thus, individual pre- and post-training scores attained by the respondents during these training programs were calculated. Mean pre-training score of respondents was 51.36 while their post-training score was 67.73 out of 100. Thus, scores of respondents were worked for the AI process- before and after the training program. The difference between the pre- and post-training scores of the respondents was 6.56 (z=6.56), which was significant. Thus, significant gain in skill of the respondents who had undergone this training was observed.